Mobile Spare-Part Application Pada Bengkel Di Kabupaten Banyuwangi - Amin, Muhammad Zainal Roisul; Adi Mulyadi; Adi Pratama Putra; Rezki Nalandari (Fakultas Teknik, Universitas PGRI Banyuwangi, 2022)
Abstract – This paper discusses about a service shop at distric of Banyuwangi. The difficulty of service shop such as manajerial, spare-part order, and delivery system was experienced. Not only car repair shop, but also motorbike repair shop. The mobile spare-part application (MSPA) is proposed with the smartphone of integration system. The MSPA is directly connected an internet to track, to delivery, to suggest the near location based on the best service. The result shows that the MSPA can reduce a queing system, spare part ordering time, and the fast delivery. The system is designed to accomplish for any problem of service shops at Banyuwangi. Keyword: Service Shop, Internet, Mobile Spare-Part Application.